Genetic Susceptibility Contributing to Periodontal and Cardiovascular Disease. (June 2017) - Aarabi, G.; Zeller, T.; Seedorf, H.; Reissmann, D.R.; Heydecke, G.; Schaefer, A.S.; Seedorf, U.
Periodontal disease (PD) and coronary artery disease (CAD) are common diseases characterized by an overaggressive inflammatory response to diverse stimuli. Whereas PD leads to destruction of the tooth-supporting structures, CAD is a chronic inflammatory condition ultimately causing myocardial infarction via narrowing and occluding of blood vessels. Classical twin studies led to the conclusion that both complex diseases have a similar degree of heritability and that a significant fraction of the genetic factors accounting for this heritability is shared. Recent genome-wide association and large-scale candidate gene studies highlight that variations in >50 genes are associated with premature CAD, while variations in only 4 genes showing nominally significant associations with aggressive periodontitis and/or chronic periodontitis have so far been identified. Remarkably, 3 of the PD loci (75%) show shared associations with CAD ( ANRIL/CDKN2B-AS1, PLG, CAMTA1/VAMP3 ), suggesting involvement of common pathogenic mechanisms. In this critical review, we highlight recent progress in identifying genetic markers and variants associated with PD, present their overlap with CAD, and discuss functional aspects. In addition, we answer why a significant fraction of the heritability of PD is still missing, and we suggest approaches that may be taken to close the gap.